Study on Oil Retention Impact Factor and Pressure Drop Characteristics of R32/PVE Mixture in Compressor Suction Line - Hu Jinting; Gu Bo; Zeng Weijie; Zhang Zhiting; Du Zhongxing (Zhileng xuebao)
This paper presents an experimental study on the oil retention and pressure drop characteristics of an R32/PVE VG68 mixture in compressor suction lines. The test samples were two smooth copper pipes with horizontal and vertical flow orientations of 10.7 mm in inner diameter. The tested conditions are saturation temperature and superheating degree (7.5/12 ℃, 7.5/6 ℃, and 10/12 °C). The refrigerant mass flux and nominal oil mass fraction (OMFno) are varied in the ranges of 90-230 kg/(m2?s) and 0-5%, respectively. The results showed that the oil retention increased with the actual oil mass fraction and mixture kinematic viscosity ratio and decreased with the refrigerant mass flux. Two consolidated databases for oil retention and pressure drop of suction lines, which involved R410A and R134a, were collected from five existing studies for comparison. Finally, based on the analysis of the oil transport mechanism, a new dimensionless parameter called the oil retention impact factor was proposed to characterize the difficulty of oil transport, which integrates the influences of geometric dimensions, working pairs, and operation parameters. It showed a relatively good relationship with the oil retention data from the amassed database and the present study.